Essays on Deleuze - Smith, Daniel W. (Daniel Warren), 1958- (Edinburgh : Edinburgh University Press, 2012)
'Gathers twenty of Smith's new and classic essays into one volume for the first time. Combining his most important pieces over the last 15 years along with two completely new essays,'On the Becoming of Concepts' and'The Idea of the Open', this volume is Smith's definitive treatise on Deleuze. The four sections cover Deleuze's use of the history of philosophy, his philosophical system, several Deleuzian concepts and his position within contemporary philosophy.' --Publisher's description.
Includes bibliographical references (p. [428]-442) and index.
Keywords: Deleuze, Gilles, -- 1925-1995 -- Criticism and interpretation